Analisis Kelayakan Usaha Tempe Kedelai GMO pada UMKM Annisa di Kubu Raya - Nugra Irianta Denashurya; Singgih Tiwut Atmojo; Irba Muhlas Sambodo (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to evaluate the financial feasibility of tempeh production using genetically modified soybeans (Genetically Modified Organisms/GMO) at the Annisa Tempe Micro, Small, and Medium Enterprise (MSME) in Kubu Raya Regency. GMO soybeans are the preferred choice for the business owner due to their stable availability and lower price compared to local soybeans. This research employs a case study approach and utilizes investment feasibility analysis methods, including Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C). The results show that the business yields an NPV of IDR 779,241,805, an IRR of 20.82%, and a Net B/C of 78.92. These indicators demonstrate that the GMO-based tempeh business at Annisa Tempe MSME is highly feasible from a financial perspective. The study also identifies key challenges such as competition in traditional markets and highlights opportunities through direct distribution and stable raw material supply. These findings are expected to serve as a reference for MSME actors, academics, and policymakers in developing sustainable GMO-based local food businesses.